Design and simulation of a novel MPCVD reactor with three-cylinder cavity. (June 2022) - Zhang, Yizhuo; Yu, Shengwang; Gao, Jie; Ma, Yong; He, Zhiyong; Hei, Hongjun; Zheng, Ke
Abstract: A novel microwave plasma chemical vapor deposition (MPCVD) reactor with three-cylinder cavity and outstanding tuning capability was proposed. The electric field and plasma in the reactor were simulated, and four geometric parameters were optimized. After optimization, the electric field intensity above the substrate exceeded 5 × 10 3 V / m (input power of 1 W), which was 1.6 times that of the similar cylindrical reactors. Only one strong plasma formed above the substrate surface with an input power of 5 kW once the gas pressure exceeds 8 kPa. But the plasma coverage area was decreased with the increase of the gas pressure. The plasma coverage area could be restored by adjusting the height difference between the adjusting mechanism 1 and 2. The frequency detuning caused by the microwave frequency changes also could be returned by adjusting the adjusting mechanisms. The subsequent experimental results showed that uniform and high-quality diamond films could be deposited under the simulation condition (5 kW and 12 kPa). It could verify the accuracy of the simulation and the excellent performance of the new MPCVD reactor. Highlights: A novel MPCVD reactor with three-connected-cylinder cavity is designed. Higher electric field intensity is reached compared with similar cylindrical reactor. Plasma coverage area can be adjusted by adjusting mechanisms. Frequency detuning problem can be solved by adjusting mechanisms. High quality diamond film can be deposited in the novel reactor at 5 kW and 12 kPa.